Structural characterization of the western flank of Domuyo volcano and its relationship with Neogene to Quaternary magmatic activity (Neuquén, Argentina) - Galetto, Antonella Tamara (2019)
This study covers the structural analysis of thewestern flank of Domuyo volcano, located in thenorthwestern sector of the Chos Malal fold and thrustbelt (36°38'15.10"S; 70°25'55.37"W).